Comparative assessment of two integrated hydrogen energy systems using electrolyzers and fuel cells. (26th November 2016) - Khalid, F.; Aydin, M.; Dincer, I.; Rosen, M.A.
Abstract: A comparative assessment is presented of two integrated hydrogen energy systems for environmentally-benign houses. The proposed energy systems use a combination of solar photovoltaic arrays and wind turbines to meet the electricity demand of the house. Energy and exergy analyses are used to assess the performance of the proposed systems. The excess electricity produced by these systems is used in the production of hydrogen through water electrolysis. In system 1, the hydrogen produced by electrolysis is utilized via a turbine to produce power during peak periods. In system 2, the hydrogen produced is utilized via a proton exchange membrane hydrogen fuel cell. A comprehensive parametric study is conducted to investigate the effects of some important parameters such as wind speed, ambient temperature, and solar irradiation on the energy and exergy efficiencies of the systems. Cost assessments of these systems are also carried out in terms of the levelized cost of electricity, and net present cost, and the proposed systems are optimized based on these parameters. The overall energy and exergy efficiencies respectively are found to be 20.7% and 21.0% for system 1, and 24.7%, and 18.9% for system 2. The levelized cost of electricity for system 1 is $ 0.431/kWh while it is $ 0.387/kWh for system 2. Highlights: Thermodynamic and economic assessments are presented of two integrated hydrogen energy systems. Proposed energy systems use a combination of solar photovoltaic arrays and wind turbines. Energy and exergy analyses are used to assess the performance of the proposed systems. Cost assessments of power generating systems are also carried out in terms of the levelized cost of electricity, and net present cost.